Pengaruh Kesehatan Mental dalam Upaya Memperbaiki dan Mengoptimalkan Kualitas Hidup Perempuan - Suwijik, Salsabila Putri; A'yun, Qurrota (Journal of Feminism and Gender Studies, 2022)
Mental health is a condition in which individuals avoid symptoms that can affect a person's psychological disruption. Mental health itself is very important and needs to be considered, because it greatly impacts the survival of the individual. Women tend to experience mental health disorders more easily than men with the possibility of two times as much. This condition will certainly be a barrier for women to achieve a better quality of life. Stress is one of the root causes of a woman's mental disruption, resulting in a decrease in thought patterns that can interfere with activities. Sufferers tend to be silent without doing any activity and it has the potential to increase their stress level. Stress risks, controlling emotions and is often seen as unimportant. Thus, it is necessary to study the effects of mental health in an effort to improve and improve the quality of life of women, both internally and externally. This article is written using a literature study method that aims to optimize the quality of life of women in achieving a healthy, prosperous, positive spirit, and resilience in facing various problems.